Traditional leaders in post-1996 South Africa, with particular reference to the Eastern Cape - De Sas Kropiwnicki, Zosa Olenka (Rhodes University, Faculty of Humanities, Department of Political Studies, 2002)
The failure of democracy in Africa can be partially attributed to the Eurocentric assumptions that belie Western recommendations for Africa. This thesis focuses on the failure of the modernisation school to account for the resiliency of tradition in the modern African state, which is described by Sklar (1991) as amounting to a form of 'mixed government', combining the traditional with the modern to create a uniquely African form of governance. This notion of a 'mixed government' is addressed from the vantage point of traditional leaders in the Eastern Cape. It maps the vacillating relationship between the chiefs, the people and the government through colonialism, Apartheid and democratisation. It concludes that although the Eastern Cape provincial government has subordinated the chiefs, this does not signify a victory for modernity over tradition because the chiefs are not a spent force. History has shown that when the government fails to act in the interests of the people, they seek an alternative authority namely, the chiefs. The ANC government's centralising tendencies have negative implications for democracy and consequently for the people. This opens up space for the chiefs to assert themselves provided they play an active role in furthering democracy, development and modernisation in the interests of the people. Hence, although ' mixed' government in the post-1996 South Africa is currently on the ANC's terms, traditional leaders may someday play a vital role in the modern democratic state.
Keywords: Tribal government -- South Africa -- Eastern Cape; Political leadership -- South Africa -- Eastern Cape; South Africa -- Politics and government